The Mediating Effect of Self-Efficacy in the Connections between Strength-Based Parenting, Happiness and Psychological Distress in Teens - Loton, Daniel J.; Waters, Lea E. (Frontiers in Psychology, 2017)
Preliminary studies of strength-based parenting (SBP), a style of parenting that seeks to build strengths knowledge and strengths use in one’s child, have reported benefits such as higher life satisfaction, subjective wellbeing, and positive emotions together with lower stress in children and teens. Two proximal mediators conveying these effects have been identified: teen’s own use of strengths and strength-based coping, along with a small moderating effect of growth mindsets relating to strengths. The current study tests the potential mediating effect of self-efficacy, a sense of agency in life, in the relationship between SBP and mental health (wellbeing and illbeing) in teens. Self efficacy has been linked to wellbeing and strengths processes in past studies and is classed as a basic human need and form of eudaimonic happiness. This study reconfirmed the adaptive benefits of SBP in a large sample of Australian adolescents (N=11,368; 59% male; Mage=14.04, SDage=1.99) sourced from 28 schools. Using structural equation modelling, SBP significantly and directly predicted higher happiness and lower depression, with direct effects falling into the 85th and 95th percentile of meta-analytically derived individual differences effect sizes. In addition, self-efficacy was a significant partial mediator, accounting for 40.0% of the total effect on happiness and 52.7% of the total effect on distress. Self-efficacy was also a full mediator in the case of anxiety, with a strong indirect effect. Results suggest that building strengths in teens can also build self-efficacy, and given the large effect sizes, that SBP is a promising leverage point for increasing teen wellbeing.